KONVERGENSI PEMBAGIAN HARTA WARIS DALAM HUKUM ISLAM - Sakirman Sakirman (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2017)
The law of Inheritance in Islamic law as one part of the law of family (al-ahwalus al-Syahsiyah) is very important in order in execution studied Division of property inheritance does not occur the error and can be implemented with seadil-fair, because by studying the Islamic inheritance laws then for Muslims, will be able to fulfil the rights relating to inheritance after it was abandoned by the muwarris (the heiress) and delivered to the beneficiary who is entitled to receive it. Thus one can avoid Sin i.e. it takes a property which is not right, because it is not ditunaikannya the Islamic law regarding inheritance. The Division of the estate in islam has been so clearly set up in al Qur'an, in surat an-Nisa. God with all his grace, has given guidelines in directing humans in terms of Division of property inheritance. Division of property is aimed at in order to be among the people who left no quarrels in doling out the estate. The estate be shared if indeed people who died leaving the property useful for others. Rules regarding marriage and Mewaris arranged in a book of civil law Act (